Gerenciamento de cadeias de suprimentos: análise da avaliação de desempenho de uma cadeia de carne e produtos industrializados de frango no Brasil - Pereira, Susana Carla Farias (2003)
Among all economics activities, agribusiness is increasing its importance with great force in the world, stimulated mainly for the growth of the population and in the demand for food. Agribusiness studies have been the focus of academic research for quite a long time. However, those studies usually have used a theoretical background, connotations, frames of reference and methodologies slightly different of those used in the research on Supply Chain Management (SCM). Most agro-industrial studies are influenced by economics theories. They usually address questions of public policy, structures of govemance and competitiveness of the industry. On the other hand, researches on SCM have a managerial concern addressing questions of operational efficiency, effectiveness, customers' needs and so on. Notwithstanding, differences on the research focus and theoretical frameworks, the systemic vision of the process - since the production of raw materials until the delivery of the product to the end consumer - is common to SCM and agro-industrial studies. The main purpose of this research is to advance in the studies of agro-industrial chains, using a management approach frequently presented in the literature of supply chain management. The unit of analysis of the research is a supply chain of poultry meat by-product in Brazil. The main approach will be the questions of management and measurement of supply chain performance.